Influence of Sugar Cane Straw Ash in Mechanical and Microstructural Characteristics of Alkali-Activated Materials Based on Red Clay Brick Waste - Bittencourt Batista, João Pedro [UNESP]; Bassan De Moraes, Maria Júlia; Mitsuuchi Tashima, Mauro [UNESP]; Akasaki, Jorge Luís [UNESP]; Payá, Jordi; Bassan De Moraes, João Claudio (American Society of Civil Engineers (ASCE), 2023)
The present paper aims to assess the feasibility of using two wastes, sugar cane straw ash (SCSA) and red clay brick waste (RCBW), in the production of a new sustainable binder for alkali-activated materials (AAM). The RCBW/SCSA mass proportions assessed were 100/0, 87.5/12.5, 75/25, 62.5/37.5, and 50/50. The activating solution was composed of NaOH and sodium silicate with a Na+ concentration of 8.3 mol.kg-1 and a SiO2/Na2O molar ratio of 1.3. Moreover, 5 wt.% of calcium hydroxide was added. Compressive strength, the volume of permeable pore space, water absorption of mortars, Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, and scanning electron microscopy with energy-dispersive X-ray spectroscopy of pastes were carried out in this study. Tests were carried out at 3, 7, and 28 days of curing at 25°C and 1 and 3 days at 65°C. Results showed that the mortars produced with RCBW/SCSA mass proportion of 50/50 presented an increase of 50% in compressive strength compared to samples with only RCBW (100/0) after 28 days of curing at 25°C (39.2 and 26.2 MPa, respectively). Moreover, the presence of SCSA content increases pore refinement and reduces water absorption. Studies on pastes showed that the SCSA favored the formation of N-A-S-H gels with higher silicon content and denser microstructure than the sample with only RCBW. Therefore, it can be concluded that the SCSA can be employed with RCBW in AAM to improve its mechanical properties and generate a denser structure.
Keywords: Alkali activation; Hardened properties; Microstructural analysis; Valorization of wastes